THE PARTICIPATION OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FORMING AN ATTITUDE OF INTER-RELIGIOUS TOLERANCE - NADA NAZOPAH; HAMDANI, HAMDANI (Jurnal Penelitian, Pengembangan Pembelajaran dan Teknologi (JP3T), 2023)
This study aims to determine the role and responsibilities of a teacher towards students who not only transfer knowledge through learning materials in the classroom but also by providing education that impacts their attitudes and behavior. SMPN 1 Gunung Sari is a junior secondary education institution that facilitates students from various economic, social, and religious backgrounds, namely Islam, Hinduism, and Christianity. This research is qualitative descriptive research which is further carried out using a case study design, namely field research using observation, interview, and documentation methods. The results of research on the role of PAI teachers in forming inter-religious tolerance attitudes at SMP Negeri 1 Gunung Sari are carried out by maximizing the teacher's function as an educator, motivator, and evaluator. These forms of tolerance include respecting greetings, mutual love, a high sense of concern, cooperation, and mutual respect and respect. Supporters were forming this tolerance attitude, namely the existence of adequate worship facilities, the realization of Cooperation Factors among school members in religious activities, and a conducive school atmosphere.